2010
DOI: 10.1016/j.expneurol.2009.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial electrode implantation produces regional neuroinflammation and memory deficits in rats

Abstract: Deep brain stimulation (DBS) is an established treatment for advanced Parkinson's disease (PD).The procedure entails intracranial implantation of an electrode in a specific brain structure followed by chronic stimulation. Although the beneficial effects of DBS on motor symptoms in PD are well known, it is often accompanied by cognitive impairments the origin of which is not fully understood. To explore the possible contribution of the surgical procedure itself, we studied the effect of electrode implantation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 80 publications
2
34
0
Order By: Relevance
“…These deficits most likely reflect side effects of the surgery, since behavioral and mnestic deficits as well as neurochemical changes have repeatedly been reported in sham-operated animals (Adams et al, 1993;Rao et al, 1999;Grossman et al, 2003;Hirshler et al, 2010). This makes the superior performance of the lesion group even more impressive, because this group also had to cope with all the general side effects caused by the present type of surgery.…”
Section: Discussionmentioning
confidence: 80%
“…These deficits most likely reflect side effects of the surgery, since behavioral and mnestic deficits as well as neurochemical changes have repeatedly been reported in sham-operated animals (Adams et al, 1993;Rao et al, 1999;Grossman et al, 2003;Hirshler et al, 2010). This makes the superior performance of the lesion group even more impressive, because this group also had to cope with all the general side effects caused by the present type of surgery.…”
Section: Discussionmentioning
confidence: 80%
“…While hippocampal tissue reduction was similar to our prior experiment (Eckart et al 2012), control and sham groups showed normal exploratory behaviour towards the displaced object during the object place recognition test, whereas the lesion group showed the expected deficit. Previously, Eckart et al (2012) found a deficit in the sham group, and other sham surgical procedures were also found to cause behavioural and mnestic deficits, as well as neurochemical changes (Adams et al 1994;Raghavendra Rao et al 2000;Grossman et al 2003;Hirshler et al 2010). The lower hippocampal volumes found in the sham group of the present study may be a result of the surgery, but since statistical analysis between control and sham animals showed no significant differences in total hippocampal volumes, it is unclear if the observed lower performance in the sham group was caused by anaesthesia, minor surgery-induced damage, or a general variability of the behavioural measures used.…”
Section: Histological Analyses and Object Place Recognition Testmentioning
confidence: 95%
“…It is vital to take all steps possible to reduce focal tissue injury, since the DBS procedure and the continued presence of the DBS leads themselves, may cause sustained widespread neuroinflammation and cognitive impairment irrespective of target region and stimulation (Hirshler et al, 2010). In this respect, the lead diameter is an important factor because it may influence the degree of tissue inflammation, microglia migration and neuronal survival in the vicinity of the electrode track (Hirshler et al, 2010;Thelin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, the lead diameter is an important factor because it may influence the degree of tissue inflammation, microglia migration and neuronal survival in the vicinity of the electrode track (Hirshler et al, 2010;Thelin et al, 2011). The LID incorporates the use of a small-diameter biocompatible guide tube (∅1.0 mm) used for implanting the stimulating lead end, after which the guide tube is implanted subcutaneously with the rest of the lead.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation